Follow-Up Analysis of Sexual Violence Case in Hospital; Before and During the Covid-19 Pandemic - Busyra Busyra; Beta Ahlam Gizela; Martiana Suciningtyas Tri Artanti (Biomedika, 2024)
Sexual violence may cause numerous health consequences, either short-term or long-term. Therefore, victims need access to healthcare facilities immediately after the incidents and follow-up care to prevent further complications. This study aims to recognize prognostic factors of sexual violence patients, analyze the follow-up visits to the hospital, and analyze how the Covid-19 pandemic affects the patients’ visits. We collected medical records data of sexual violence patients that visited the hospital during 2017-2021. Prognostic factors, comprised of demographic profile and case characteristics, were analyzed with follow-up visits to the hospital. Our subjects were 113, 108 female and five male. Most female patients were aged 14-17 years and were secondary school students, while all male patients were aged 6-13. Most perpetrators were known to the victims while the incident places were mainly at their places. Penetration, anogenital injury, and psychological symptoms were present in most patients. We found that 24 (21.2%) patients appeared in a follow-up visit. We found no difference in patient visits before and during the Covid-19 pandemic. However, statistical analysis of follow-up visits indicated a significant relationship with the follow-up plan.